Effect of Ti content on structure and mechanical properties of Cr–Ti–N films. (3rd August 2017) - Feng, X.; Zhou, H.; Wan, Z.; Zhang, K.
Abstract : Cr–Ti–N films are deposited on the surface of Ti6Al4V alloy by unbalanced multi-targets reactive magnetron sputtering. In this study, the effect of the Ti content on microstructure, hardness, modulus and tribological behaviours of Cr–Ti–N films are systematically investigated. The XRD shows that with the increasing of Ti content, the phase structure evolves from Cr + Cr2 N + TiN → amorphous → FCC solid solution. The hardness and modulus of Cr–Ti–N films are increased by improving Ti content in the films and Cr32.5 Ti24.6 N42.9 film reaches maximum values of 25.8 and 362.7 GPa, respectively. The wear rate of the Cr–Ti–N films is gradually decreased with increasing Ti content and the Cr32.5 Ti24.6 N42.9 film decreases five times and 25 times than Cr50.7 Ti10.1 N39.2 and substrate, respectively.